Review of problems in the development of rail tourism in Taiwan, on the example of the Alishan Forest Railway - Chong, Daniel Ka Leong * (University of Oradea, Romania, 2019)
Rail tourism is significant in boosting Taiwan’s tourism industry with more than 560,000 tourists visited Alishan railway, one of the most significant heritage rail tourism sites in 2018. However, recently more attentions and efforts were being put on High-Speed-Rail instead of heritage rails in Taiwan. As the Taiwan Railways Administration launched the 10 years plan in replacing the heritage rail, it has raised the question of sustainability of the heritage rail tourism in Taiwan. The study aims to assess the challenges faced in developing heritage rail tourism in Taiwan by using the Porter’s Diamond Model as the assessment criteria. The data was collected through a variety of methods inclusive of interviews, observations, and review of challenges faced in the process of preparing the existing heritage railways for the future of Taiwan’s rail tourism. This study found that despite the popularity, financial subsidies and extensive promotion effort by Taiwan Railways Administration, the heritage rail tourism in Taiwan is still facing difficulties in remaining sustainable in the long-run due to inefficient firm strategy, poor pricing strategy, and also non-user-friendly online ticketing system.